2020
DOI: 10.31080/asds.2020.04.0806
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Chitosan Nanoparticles on the Ultra-Structure of Dentinal Wall: A Comparative In vitroStudy

Abstract: This study was conducted to evaluate the efficacy of 0.2% Chitosan Nanoparticles (CNPs), CNPs/EDTA (1:1) and 17% EDTA on smear layer removal ability.Methods: Fifteen extracted human permanent mandibular premolars with single canals were decoronated and biomechanically prepared using protaper next rotary system and 2.5% Sodium hypochlorite, then randomly distributed according to the final irrigation protocol into 3 group; Group I (0.2% CNPs), Group II (CNPs/EDTA) (1:1), and Group III (17% EDTA). A standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It can be explained that the ERB sealer employed in this study (AH 26) consisted of formaldehyde, epoxy resin, and hexamethylenetetramine, besides being antibacterial, they are also toxic. 23,27 This cytotoxic effect in this study was only observed after 24 hours. This effect may decline if the longer observation is undertaken because the release of formaldehyde is reduced on the 7th day.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…It can be explained that the ERB sealer employed in this study (AH 26) consisted of formaldehyde, epoxy resin, and hexamethylenetetramine, besides being antibacterial, they are also toxic. 23,27 This cytotoxic effect in this study was only observed after 24 hours. This effect may decline if the longer observation is undertaken because the release of formaldehyde is reduced on the 7th day.…”
Section: Discussionmentioning
confidence: 50%
“…It might be due to the presence of antibacterial components, such as hexamethylenetetramine and formaldehyde in the ERB sealer used in this study (AH 26). 23 The more concentration addition of the chitosan to ERB sealer may not affect the antibacterial activity as shown in this study. 24 ADTwas selected to evaluate antibacterial properties in this study since this technique has been widely used to evaluate the antibacterial activity of sealers and offers many advantages, such as simplicity, low cost, the ability to test enormous numbers of microorganisms and antimicrobial agents, and the ease to interpret results provided.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The explanation of these results can be demonstrated by higher density of tubules within the coronal third compared to the middle as well as apical thirds [56] . Added to that, the impact of EDTA on the removal of smear layer declines while moving from coronal to apical [57] . This could be associated with increased number of opened dentinal tubules in the coronal third therefore more resin tags and higher AH plus bond [52,54] .…”
Section: Discussionmentioning
confidence: 99%